Vibration analysis of cantilever beam for damage detection - Marjan Djidrov; Viktor Gavriloski; Goce Tasevski (My University, 2014)
Mechanical structure during their functional operations may be vulnerable to damages and therefore cannot to be guaranteed definite fault free operational mode and successful exploitation. In this paper, vibration analysis and frequency response analysis of cantilever aluminium beam with bonded piezoelectric transducer are presented by using finite element method in finite element analysis software ANSYS. Cantilever beam vibration response are analysed and numerical results of undamaged beam model are compared to different scenarios of damage presence in structure, by location and depth of single transversal crack. Technique is based on the idea, if a crack appears in mechanical structure, this can be recognized as changes in the physical properties, which leads to cause changes in the modal properties of the structure.
Keywords: damage detection, vibration analysis, frequency response